Pest status, abundance and diversity of insect pests harboring on soybean (Annals of Bangladesh Agriculture, 2025)
Check lists of insect pests of soybean and their succession in relation to crop stages are scanty in Bangladesh. A study was conducted during January to April 2023 at the Department of Entomology, Gazipur Agricultural University (GAU), Gazipur to know the prevalence of the insect pests and their status on soybean. According to rate of plant infestation, flea beetle (35.7%), jassid (34.4%), whitefly (27.5%), soybean looper (33.6%) and pod borer (36.9%) were categorized as the major pests while leaf miner (15.5%), leaf beetle(15.2%), epilachna beetle (15.8%), grasshopper (17.6%), aphid (11.8%), green stink bug (11.2%), hairy caterpillar (16.7%), leaf roller (17.0%), stem fly (19.5%), thrips (13.1%) and weevil (13.9%) were categorized as the minor pests. The pest insects were most abundant in mid-March (24.7±5.3) when the plant was pod initiation stage. The richness (2.5±0.1), diversity (2.6±0.1) and evenness (0.94±0.2) of insect pests were also the highest in mid-March. The rank abundance of the harbored arthropods showed that the pod borer occupied the top rank (19.0%) in soybean field.Ann. Bangladesh Agric. 29(1): 13-22